2004
DOI: 10.7205/milmed.169.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CO2Accumulation in Respiratory Protective Devices

Abstract: A simple mathematical model was developed to grade the results of the fraction of inspiratory CO2 levels in respiratory protective devices (RPDs). Using this model, the level of FiCO2 of two chemical warfare RPDs was monitored during the examination of 54 young male volunteers at rest and exercise. No set of results distributed in a normal Gaussian mode; therefore, parametric statistics could not be used to analyze the group's results. Yet the model allowed simple and insightful evaluation of the results, stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…These findings support research conducted by Kloos and Lamonica (1966) and Luria et al (2004) who found low work rates during RPD use was associated with CO 2 accumulation. A previous study by Luria et al (2004) attributed this to a rise in ventilation and lower dead space during higher exercise efforts.…”
Section: Discussionsupporting
confidence: 81%
“…These findings support research conducted by Kloos and Lamonica (1966) and Luria et al (2004) who found low work rates during RPD use was associated with CO 2 accumulation. A previous study by Luria et al (2004) attributed this to a rise in ventilation and lower dead space during higher exercise efforts.…”
Section: Discussionsupporting
confidence: 81%